Peer-To-Peer Corrective Feedback In A Group Interaction - Abdul Raof, Abdul Halim; Che Razali, Sulia Masturina (2010)
The study investigated the provision of corrective feedback and learner repair of errors following feedback in interactional context of peer-to-peer conversations, particularly in a group setting. A total of four students in their early twenties participated in the study. These students are participants of the “Friends of English” (FoE) programme conducted by Centre of Teaching and Learning, Universiti Teknologi Malaysia. The relationship among error types, feedback types and learner repairs were examined. The interaction between these students in a group setting was recorded using Sony Sound Forge. The recorded interactions were transcribed and coded for types of errors (Syntactic / Lexical / L1), types of negative implicit feedback (Negotiation / Recasts) and learner repairs. Findings indicate that the mentor focused on recasts. He provided implicit negative feedback in the form of recasts to all three types of learner errors while engaging in the discussions. The majority of L1 errors were corrected followed by Lexical errors. Syntactic errors had the least number of repairs. Lexical error was the focus of the mentor as over half of Lexical errors received feedback followed by Syntactic error and L1 use.